Correlations in distribution and concentration of calcium, copper and iron with zinc in isolated extracellular deposits associated with age-related macular degeneration - Jane M. Flinn; Peter A. Kakalec; Ryan Tappero; Blair F. Jones; Imre Lengyel (2014)
Examining the relationship between zinc, calcium, iron and copper in isolated sub-RPE deposits highlighted the diverse role these metals might play in conditions like age-related macular degeneration.